METHOD OF TREATMENT FOR ANAL CANCER AFFECTING THE SKIN - O. I. Kit; L. Ya. Rozenko; E. M. Frantsiyants; M. A. Gusareva; N. G. Kosheleva; A. A. Solntseva; Yu. N. Krokhmal (Сибирский онкологический журнал, 2019)
The extent of surgery for anal rectal cancer (ARC) is determined by the clinical efficacy of neoadjuvant chemoradiotherapy (CRT). An approach using medium intensity ultrasound combined with chemotherapy was developed. Advantages of sonodynamic chemotherapy (SD CT) were evaluated to improve the CRT efficacy and the quality of life of patients with ARC affecting the skin.Material and methods. 34 patients with morphologically verified сТ2–3N0–1M0 ARC received 2 cycles of polychemotherapy (PCT): intravenous bolus of mitomycin C 10 mg/m2 on days 1 and 29 + continuous infusion of 5-fluorouracil 1000 mg/m2 daily on days 1–4 and 29–32. Patients received CRT 3 weeks after the second PCT cycle. Prior to each session of standard external and intracavitary irradiation, 18 patients of the main group received a 2-hour extemporaneous mixture to the primary tumor site: 5 mg of the Coletex SP-1 hydrogel material with propolis based on sodium alginate plus 100 mg of gemcitabine-medac together with mid-frequency ultrasound (0.88 MHz, I =1.0 Вm/cm2, Patent No. 2638616). 16 controls received capecitabine 825 mg/m2 orally twice a day with 12-hour intervals during the radiation course.Results. Controlled general clinical effect after external irradiation + SD CT in the main group was 25.7 % (p<0.05) higher than in controls, and complete regression was 1.4 times more frequent (77.8 % vs. 56.2 %). Radical surgery after CRT was necessary only in 11.1 % cases in the main group vs. 43.8 % in controls (p<0.05). No local recurrences were observed during 612 months in 16 patients of the main group without surgery, while 22.2 % (p<0.05) of controls showed local recurrence. The rates of pelvic relapses and distant metastases were similar in both groups.Conclusion. The positive effect of the proposed method for ARC treatment is determined by the combination of therapeutic factors including the action of a radiosensitizing agent introduced into tumor tissues.